2009
DOI: 10.1107/s0108270109045570
|View full text |Cite
|
Sign up to set email alerts
|

Tetrakis(μ-triisopropylsilanethiolato)-1:2κ4S:S;2:3κ4S:S-bis(triisopropylsilanethiolato)-1κS,3κS-trizinc(II)

Abstract: The title compound, [Zn(3)(C(9)H(21)SiS)(6)] or [((i)Pr(3)SiS)Zn(mu-SSi(i)Pr(3))(2)Zn(mu-SSi(i)Pr(3))(2)Zn(SSi(i)Pr(3))], is the first structurally characterized homoleptic silanethiolate complex of zinc. A near-linear arrangement of three Zn(II) ions is observed, the metals at the ends being three-coordinate with one terminally bound silanethiolate ligand. The central Zn(II) ion is four-coordinate and tetrahedral, with two bridging silanethiolate ligands joining it to each of the two peripheral Zn(II) ions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…17 The structural studies confirmed that as a result of the syntheses we have obtained heteroleptic silanethiolate com-plexes of nickel(II), cobalt(II), and zinc(II). It is certainly possible to obtain homoleptic chalkogenolates of these metals; such as Zn, Ni, Co alkyl-and arenethiolates, 12,[18][19][20][21] Zn silanethiolates 22 and also one Zn silanetelluroate 23 were described. Among various aggregation patterns small M 2 S 2 rings are often found [18][19][20]22,23 as well as ubiquitous clusters of higher nuclearity.…”
Section: Crystal Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The structural studies confirmed that as a result of the syntheses we have obtained heteroleptic silanethiolate com-plexes of nickel(II), cobalt(II), and zinc(II). It is certainly possible to obtain homoleptic chalkogenolates of these metals; such as Zn, Ni, Co alkyl-and arenethiolates, 12,[18][19][20][21] Zn silanethiolates 22 and also one Zn silanetelluroate 23 were described. Among various aggregation patterns small M 2 S 2 rings are often found [18][19][20]22,23 as well as ubiquitous clusters of higher nuclearity.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…It is certainly possible to obtain homoleptic chalkogenolates of these metals; such as Zn, Ni, Co alkyl-and arenethiolates, 12,[18][19][20][21] Zn silanethiolates 22 and also one Zn silanetelluroate 23 were described. Among various aggregation patterns small M 2 S 2 rings are often found [18][19][20]22,23 as well as ubiquitous clusters of higher nuclearity. 18,21,22 Homoleptic tri-tert-butoxysilanethiolate complexes of cadmium and mercury were obtained and characterized by Wojnowski and co-workers.…”
Section: Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Silanethiolate complexes with less sterical hindrance about the silicon atom were usually reported as the potential precursors to metal–sulfur clusters and particles. These included trimethylsilanethiolates, triisopropylsilanethiolate, and triphenylsilanethiolates. , Mixed-ligand silanethiolate cadmium complexes were probed as precursors of CdS thin films …”
Section: Introductionmentioning
confidence: 99%